The effectiveness of the leadership transformation program among off-campus student at University Malaysia Pahang - Rohana, Hamzah; Nurul Ain Fatehah, Baharuddin; Zuraina, Ali; Muhammad Afzamiman, Aripin (2018)
The social issue involves university students are quite serious as reported in mainstream media and social media. All parties need to work together to help our students before this issues turn to be more serious. Focus should give more to off-campus students that are living outside of the campus since they are easily to be affected with negative influence from their surroundings. To identify the problem, preliminary study has been carried out. Result from the study shows that there are four major problem involve among them which is self-management; relationship with the Creator; social relationship with housemate; and house management. Therefore, in order to handle the problem an intervention program has been design named Transformation Leadership Program for Off-Campus Students. This study used mix method design. However, for this article purposes, finding from quantitative data will be reported. Furthermore, this study also apply pre experimental design (one group pre and post-test) since the main limitation for this study is to get the sample randomly and to ensure their commitment to the end of the program. 40 respondents involved as the respondents. Result shows that there is no significant different for variable measure respondents’ belief in Creator although the mean value was increase. However, there were significant improvements in the other three variables assessed namely the transformation of self-leadership, the transformation of social leadership (housemate) and the transformation of environment leadership (house management). Therefore, this program helps off-campus students to understand and make a connection between the value of belief in God (spiritual intelligence) with the exercise of social responsibility as a leader to oneself, others and the environment (their house) practically. Therefore, it is a hope for this program to be implement and benefited by more off-campus students and contribute to build up more holistic and comprehensive university students’ management system in future.